LEND ME YOUR EARS: DEVELOPING LISTENING SKILLS - Z. N. Patil (Leksika: Jurnal Bahasa, Sastra dan Pengajarannya, 2012)
Listening occupies a central place in communication in everyday situations as well as business settings. We spend more time listening than we spend speaking, reading and writing. Most of our knowledge of the world derives from listening input. In spite of the centrality of listening, it has received an unfair treatment in second and foreign language classrooms. On the other hand, reading and writing have received a favorable treatment. The present paper discusses why it is imperative to develop listening skills in our learners. Elaborating on the ingredients of effective listening and causes and consequences of poor listening, the paper suggests some remedial measures and exercises to improve the listening skills of learners of English as a second and foreign language.